VALUE RELEVANCE-EVIDENCE FROM FOOD INDUSTRY - Saković, Dušan; Ilić, Miloš (Economics of Agriculture, 2018)
The aim of the paper is to determine the correlation between the changes in the values of the selected analytical indicators, based on the financial statements and the change in the market value of companies, expressed through the value of the market value multipliers. The focus of research is on companies operating on the European markets within the food industry. The research methodology implies the use of regression analysis where the market multipliers of the selected enterprises will be set as dependent variables, and the analytical indicators are proposed as independent variables. The expected results should indicate the existence of value-relevant information in the financial statements of companies from food industry, which will serve all stakeholders for more efficient decision-making that is related to this industry sector. Data used in the research are acquired from European equity markets.